Guillermo Rochabrún´s Bet on Capital. To Develop a Scientific Research Programme for the Social Sciences - Paredes Valderrama, Álvaro (2023)
The goal of this paper is twofold: First, it seeks to describe the way in which Rochabrún theorizes Marx´s approach in his book Marx´s Capital. Affirmation and Reframing (2021). Second, it seeks to evaluate the relevance of Rochabrún’s theoretical work to the social sciences today. The paper is divided in two parts. In the first part, Rochabrún´s reconstruction of historical materialism is discussed as well as the way in which such reconstruction serves as the basis for Capital´s theory of capitalism. This part also discusses how Rochabrún’s work brings the study of the private nature of social relations to its ultimate consequences, enhancing the understanding of capitalist reproduction as both an analytical moment and instance of reality. This leads him to refuse the “general law of capitalist accumulation” and to harmonize the theory of Capital with the history of capitalism. The second part of the paper uses the methodology of Lakatos´s scientific research program to assess Rochabrún´s theoretical proposal. It is argued that Rochabrún´s work contains greater heuristic power compared with the Marxist theorizations that followed Marx´s death as it allows us to propose a more theoretically founded hypotheses about the definitive exhaustion of capitalism.